Altered corticostriatal pathway in first-episode paranoid schizophrenia: Resting-state functional and causal connectivity analyses. (28th February 2018) - Huang, Huan; Shu, Chang; Chen, Jun; Zou, Jilin; Chen, Cheng; Wu, Shihao; Xiao, Ling; Liu, Zhongchun; Wang, Huiling; Zhou, Yuan; Wang, Gaohua; Jiang, Tianzi
Abstract: Neuroimaging studies suggest the abnormal structure and function of basal ganglion may contribute to the pathophysiology of schizophrenia. However, little is investigated about the both aberrant functional and causal connectivity of striatum in first-episode paranoid schizophrenia (FEPS). Resting-state functional magnetic resonance imaging was used to characterize the functional connectivity (FC) and casual connectivity within the corticostriatal circuit in 31 patients with FEPS and 33 healthy controls. Degree centrality (DC) was used to explore the regions influenced in schizophrenia at the whole-brain level. Subsequently, a seed-based Granger causality analysis was performed to analyze the causal connectivity. We identified reduced DC of the bilateral putamen in the patients, compared to the controls. In the causal connectivity analysis, we found causal dysconnectivity between the putamen and several regions of default mode network, right orbital part of inferior frontal cortex and right fusiform in the patients. Further, the abnormal causal effect was associated with cognitive impairment in FEPS. The present study highlighted the abnormal functional and causal integrity of the striatum in the patients with FEPS during resting state and suggests a potentially implicated role for the cortical-striatal circuit, especially the striatal-default mode network loop, in the pathophysiology of schizophrenia. Highlights: The aim of the present study was to use resting-state functional magnetic resonance imaging to characterize the alterations of functional connectivity and causal connectivity within cortical–striatal circuit in first-episode paranoid schizophrenia. 31 patients and 33 healthy controls matched for age, gender, and education were enrolled in this case-control cross-sectional study. This study highlighted the abnormal functional and effective integrity of the striatum in the patients with first episode paranoid schizophrenia during resting state and suggests a potentially implicated role for the striatum in the pathophysiology of schizophrenia.